Analysis of the Influence of Service Quality and Customer Relationship Management on Customer Loyalty - David Pranata Pakpahan (CV Raskha Media Group, 2025)
This study aims to analyze the influence of service quality and customer relationship management (CRM) on customer loyalty. In a highly competitive business environment, maintaining customer loyalty has become a crucial strategy for organizational sustainability. Service quality represents the company’s ability to consistently meet customer expectations through tangible aspects, reliability, responsiveness, assurance, and empathy. Meanwhile, CRM emphasizes the strategic management of customer information and relationships to enhance satisfaction and retention. Using a quantitative approach, data were collected through questionnaires distributed to customers who had experienced the company’s services. The results reveal that both service quality and CRM have a significant positive effect on customer loyalty. Service quality directly enhances customer satisfaction, which subsequently fosters emotional attachment and repurchase intention. Additionally, CRM strengthens long-term relationships by improving communication, personalization, and customer engagement. The findings indicate that customer satisfaction acts as a mediating variable linking service quality and CRM with loyalty. This study concludes that organizations must integrate superior service delivery with effective CRM strategies to build sustainable customer loyalty. The implications suggest that managers should invest in employee training, digital CRM systems, and continuous service evaluation to maintain competitiveness. The research contributes theoretically by reinforcing the link between service quality, CRM, and loyalty, and practically by providing a model for loyalty management.